Simulating Behavior Diversity in BioCrowds - Knob, Paulo; Musse, Soraia Raupp (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI), 2019)
Most of the techniques available nowadays for crowd simulation are focused on a specific situation, e.g. evacuation inhazardous events. Very few of them consider the cultural and personality aspects present in a society to determine the behavior of agents. Therefore, this work aims to build a framework able to deal with different cultural and personality traits as input, and translate them into a group parametrization, which is going to determine the behavior of groups and crowds in virtual environments. Also, we include in BioCrowds a comfort response for agents, in terms of density and thermal characteristics of the environment. Results indicate that the cultural/psychological mappings seem promising, since agents were able to perform as intended. Additionally, agents were able to react due to thermal and density comfort, improving their ability to react to environmental changes.